China's Military Modernization and its Implications on Global Security - Ahmad Sheikh, Javaid (International Journal of Psychosocial Rehabilitation, 2019)
Information operations and cyberwarfare are now recognized as vital modern components of China's military modernisation. With significant ramifications for the dynamics of international security, China's quick military modernisation has been a focus of attention. This research paper offers a thorough examination of China's ongoing military modernization initiatives and their varied impacts on the wider international security environment. This research paper delves into the multifaceted landscape of China's military modernization and its far-reaching consequences for global security. The paper systematically examines the historical context, objectives, components, and implications of China's ongoing efforts to modernize its military capabilities. By analyzing the geopolitical, economic, technological, and ethical dimensions, this study provides a comprehensive overview of the challenges and opportunities posed by China's evolving military prowess.